How Financial Performance Affects the Value of Conventional National Commercial Banks in Indonesia - Sochib, Sochib; Liyundira, Fetri Setyo; Yulianti, Ani (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
The objective of this study is to investigate the impact of financial performance on the firm value of Indonesia’s national commercial banks throughout the years 2017 to 2023, which includes the COVID-19 pandemic. Financial performance is reflected using the Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) indicators, while firm value is reflected by the Price to Earnings Ratio (PER), Operating Expense to Operating Income (OEOI), and Non-Performing Loan (NPL). The analysis method used is Partial Least Squares Structural Equation Modeling (PLS-SEM). The population in this study is a national conventional banking entity listed on the IDX in 2017-2023. Sampling using a purposive sampling technique so that a sample of 23 companies was obtained with 161 observations. The study finds that financial performance negatively affects firm value, revealing a gap between theory and actual outcomes. While ROA declined, PER increased during the study period, indicating that firm value in the banking sector is not solely influenced by short-term profitability. Instead, it is also shaped by market expectations of economic recovery and government policies. These findings offer useful insights for improving management strategies, strengthening risk control, and enhancing long-term firm value.